Evaluating an estimated new Keynesian small open economy model - Malin Adolfson; Stefan Laséen; Jesper Lindé; Mattias Villani (Sveriges Riksbank, 2007)
This paper estimates and tests a new Keynesian small open economy model in the tradition of Christiano, Eichenbaum, and Evans (2005) and Smets and Wouters (2003) using Bayesian estimation techniques on Swedish data. To account for the switch to an inflation targeting regime in 1993 we allow for a discrete break in the central bank's instrument rule. A key equation in the model - the uncovered interest rate parity (UIP) condition - is well known to be rejected empirically. Therefore we explore the consequences of modifying the UIP condition to allow for a negative correlation between the risk premium and the expected change in the nominal exchange rate. The results show that the modification increases the persistence and volatility in the real exchange rate and that this model has an empirical advantage compared with the standard UIP specification.
Keywords: E17; C11; C53; 330; DSGE; VAR; VECM; Open economy; Bayesian inference; Zentralbank; Geldpolitik; Inflationssteuerung; Wechselkurspolitik; Zins; Keynesianismus; Allgemeines Gleichgewicht; Schweden